2000
DOI: 10.1007/s001670050005
|View full text |Cite
|
Sign up to set email alerts
|

The Gore-Tex prosthetic ligament as a salvage procedure in deficient knees

Abstract: The purpose of this study was to evaluate the results of prosthetic ligament replacement of the anterior cruciate ligament (ACL) or posterior cruciate ligament (PCL) with the Gore-Tex polytetrafluorethyene prosthesis (W.L. Gore and Co., Flagstaff, Ariz. ) in 52 patients (54 knees). All patients sustained multiple (failed) knee operations or had knees with gross instability. Twenty-eight (29 knees) of the 52 patients (54%) in whom the Goretex prosthesis was still in situ were available at a minimum follow-up of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…54 Although the only clinical report in which Gore-Tex was used for CC stability showed good results, 41 complications associated with Gore-Tex implants have been reported in other orthopaedic applications, particularly ACL reconstruction. Although early reports on the use of Gore-Tex for ACL reconstruction were encouraging, [7][8][9]17,31,53 other studies showed mixed results with high failure rates, 18,19,45,47,58 often associated with tibial and femoral osteolysis. The exact mechanism of osteolysis seen with Gore-Tex implants is not known.…”
Section: Discussionmentioning
confidence: 96%
“…54 Although the only clinical report in which Gore-Tex was used for CC stability showed good results, 41 complications associated with Gore-Tex implants have been reported in other orthopaedic applications, particularly ACL reconstruction. Although early reports on the use of Gore-Tex for ACL reconstruction were encouraging, [7][8][9]17,31,53 other studies showed mixed results with high failure rates, 18,19,45,47,58 often associated with tibial and femoral osteolysis. The exact mechanism of osteolysis seen with Gore-Tex implants is not known.…”
Section: Discussionmentioning
confidence: 96%
“…[6][7][8] Permanent synthetic ACL prosthesis including Gore-Tex prosthesis, Stryker-Dacron ligament, and Kennedy ligament augmentation device can be used, and may show satisfactory performance in the short term but they tend to deteriorate and fail in the long term. [9][10][11] In addition, a prosthesis-induced disturbance in the release of cytokine by lymphocytes can cause defects in the host defense against a bacterial infection. various growth factors have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the prostheses used for ACL reconstruction have failed as they showed an adverse effect on the cartilage and caused in some cases a marked synovialitis. Though their biomechanical Properties were excellent initially, most of the prostheses had the problem of degradation, tunnel widening and high failure rates after several years (Muren et al, 2005;Roolker et al, 2000). Compared to the biomechanical properties of ligaments, meniscus tissue is even more complex and not surprising, the middle to long term results of the artificial meniscus constructs show different results from one study to the other, but in general do not reach the anatomic, biomechanical results (Buma et al, 2007).…”
Section: Introductionmentioning
confidence: 99%